Supervisi Akademik Mampu Meningkatkan Kemampuan Guru dalam Pembelajaran di SDN Sembungharjo 02 Semarang - Mutasaroh, Mutasaroh (Jurnal Inovasi Pembelajaran di Sekolah, 2022)
The problem in this research is the incomplete preparation of teachers in teaching. Every teacher is required to make learning plans such as lesson plans, semester programs, annual programs, syllabus and other learning tools. From the results of the assessment of academic supervision in the early stages of 10 teachers at SD Sembungharjo 02, the following data were obtained: 1 teacher (10%) with good grades, 4 teachers (40%) with sufficient scores and 5 people (50%). This research design uses a classroom action research approach (School Action Research). The population in this study were all teachers of SDN Sembungharjo 02 in 2021/2022. The sample in this study used a saturated sample, that is, the sample includes the entire research population. The data analysis in this study included 2 cycles, each cycle consisting of 4 stages, namely: (1) the planning stage of the action program, (2) the implementation of the action program, (3) the observation of the program, (4) reflection. The results of this study indicate that, (1) In the pre-cycle the average value of teachers in academic supervision is 59.4 which means that teachers' academic scores are still very low; (2) in the first cycle the average academic supervision score was 71.1, which means that in the first cycle there was an increase in the teacher's academic supervision results from the pre-cycle supervision results; (3) in the second cycle, the average academic supervision score was 85.2, which means that most of the teachers had planned their learning to be better. With an average of 85.2, it has met the predetermined research standard of 70%, so there is no need to proceed to cycle 3. Based on these results, it can be concluded that regular academic supervision can improve teacher performance at Sembungharjo 02 Elementary School in the first semester of the 2021/2022 academic year. Suggestions in this study are administrative supervision is absolutely necessary for school progress and better learning outcomes.